A phenomenological study: management of independent adiwiyata schools - Trisiani Trisiani; Rosalina Br Ginting; Muhtarom Muhtarom (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
The Adiwiyata school program does not always run smoothly. Teachers find it difficult to consistently demonstrate environmentally conscious behavior, and monotonous and unvaried activities reduce the interest of students, teachers, and school staff. The purpose of this study is to describe and analyze the management of Adiwiyata Mandiri School at SMP Negeri 31 Semarang. The research approach used is qualitative. The type of research is phenomenology. The qualitative research design consists of three stages: orientation, focused exploration, and data analysis. Data collection techniques include interviews, observation, and documentation. The data analysis technique used is Miles and Huberman's data analysis, which is a systematic and interactive method for analyzing qualitative data. The results of the study show that: First, planning was carried out by compiling school environmental assessments and environmental action plans. The principal then formed a school Adiwiyata team and conducted an initial identification and assessment of the school environment. Second, Organization was carried out by determining teacher resources, planning and developing the organization, assigning and delegating authority. Third, Implementation was carried out by directing and motivating the principal, implementing independent Adiwiyata school management, supervising the principal, and reporting on the success of the independent Adiwiyata school. Fourth, Supervision of independent Adiwiyata school management was carried out through evaluation of the results of independent Adiwiyata school management, correction, and follow-up. The author suggests that school principals pay more attention to implementation and evaluation. Teachers are required to always be ready to carry out activities.